2020
DOI: 10.1021/acs.jchemed.0c00668
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perceptions Regarding the Abrupt Transition to Online Learning During the COVID-19 Pandemic: Case of Faculty of Chemistry and Hydrocarbons at the University of Boumerdes—Algeria

Abstract: In recent months, universities around the world have been forced to cancel courses and close their doors due to the growing coronavirus epidemic. Following the government’s precautions, Algerian students were bound to quarantine regulations for their safety. Thus, they unexpectedly switched to online learning instead of face-to-face learning. Our objective of this exploratory study is to investigate the perceptions of Algerian university students regarding the abrupt transition to online learning amid the COVI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 25 publications
4
82
3
1
Order By: Relevance
“…Students missed appropriate interaction with classmates and instructor (Online Student Survey, 2020), which had also claimed in several previous studies (Bisht et al, 2020;Khalil et al, 2020). On the contrary, Alawamleh et al (2020) and Blizak et al (2020) found that most students preferred traditional direct classes in the classroom instead of virtual classes. In addition, those studies found that participants did not discern comfort in virtual classes, and participants argued that conventional classes are better than online classes.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Students missed appropriate interaction with classmates and instructor (Online Student Survey, 2020), which had also claimed in several previous studies (Bisht et al, 2020;Khalil et al, 2020). On the contrary, Alawamleh et al (2020) and Blizak et al (2020) found that most students preferred traditional direct classes in the classroom instead of virtual classes. In addition, those studies found that participants did not discern comfort in virtual classes, and participants argued that conventional classes are better than online classes.…”
Section: Discussionmentioning
confidence: 61%
“…Sometimes, they disconnected from online class due to electricity and faced challenges communicating with teachers and classmates, and the argument had supported by similar studies in Nepal (Subedi et al, 2020). On the other hand, Blizak et al (2020) mentioned that students faced difficulty participating in online classes due to the lack of gadgets. We also noticed similar problems among Bangladeshi students in accessing suitable devices to access online schooling.…”
Section: Discussionmentioning
confidence: 99%
“…Some have highlighted students' negative perception of online learning and their lack of learning motivation and digital competences (Blizak et al, 2020;Bozkurt & Sharma, 2020). A growing number of articles have also discussed how to prevent cheating behaviors in online assessments, assuming students to be potential cheaters (J.…”
Section: Prevailing Pessimism About Student Experiences During the Pamentioning
confidence: 99%
“…Siswa lebih banyak menyukai pembelajaran luring karena siswa terbiasa dipandu guru dalam pembelajaran bahkan belum siap belajar mandiri jarak jauh (Churiyah et al, 2020) (AGORMEDAH et al, 2020. Siswa lebih senang belajar tatap muka dibandingkan dengan daring pada pokok bahasan hidrokarbon (Blizak et al, 2020). Bagi siswa pembelajaran daring tidak lebih menarik dibandingkan pembelajaran tatap muka (El Firdoussi et al, 2020).…”
Section: Metode Penelitianunclassified